Effect of immunomodulating treatment (usage of DMARDs) in rheumatoid arthritis on depression - Magdalena Kozyra; Patryk Zimnicki; Natalia Śmiech; Justyna Kaczerska; Martyna Nowińska; Joanna Milanowska (Kazimierz Wielki University, 2020)
Introduction: There are similarities in the level of cytokines in Rheumatoid Arthritis (RA) and depression. That is why, during usage of Disease-modifying antirheumatic drugs (DMARDs) which modulate the the level of cytokines may influence both depression and RA The aim of the study: The aim of this article is to find out in what way do the DMARDs influence the depression. Material and method: The research of the scientific articles was made on a database of PubMed and Google Scholar. Description of the state of knowledge: The results show, that most of the DMARDs may decrease the level of depression what is connected with the way of how these medicines influence the level of cytokinese. There are some exceptions such as Chloroquine and anakinra which will increase the probability of depression and there is adalimumab where the is case report which presents one case of appearance of depression after taking this medicine. Summary: This article gathers scientific research on the influence of DMARDs on depression. It shows the mechanisms, and possible ways in which these medicins influence both RA and depression. For some of the DMARDs there are no scientific articles which would include their influence on depression and it might be the way of further researches.